The impact of a computerised test of attention and activity (QbTest) on diagnostic decision-making in children and young people with suspected ADHD: single-blind randomised controlled trial - Hollis, Chris; Hall, Charlotte L.; Guo, Boliang; James, Marilyn; Boadu, Janet; Groom, Madeleine J.; Brown, Nikki; Kaylor-Hughes, Catherine; Moldavsky, Maria; Valentine, Althea Z.; Walker, Gemma M.; Daley, David; et al. (Wiley, 2018)
Background: Diagnosis of attention deficit hyperactivity disorder (ADHD) relies on subjective methods which can lead to diagnostic uncertainty and delay. This trial evaluated the impact of providing a computerised test of attention and activity (QbTest) report on the speed and accuracy of diagnostic decision making in children with suspected ADHD.